PENGARUH DEMOGRAFI DAN SOSIOEKONOMI PADA KEJADIAN KEKURANGAN ENERGI KRONIK IBU HAMIL DI KOTA METRO PROVINSI LAMPUNG - Anggraini, Yetti (Politeknik Kesehatan Tanjungkarang, 2013)
Yetti Anggraini1)1)Jurusan Kebidanan Poltekkes Kemenkes Tanjungkarang ABSTRACT: Demographic andSocioeconomicinfluenceon theincidence ofChronic EnergyDeficiencyPregnant MotherInMetroCityLampung Province.This study aimed to analyze the influence of demographic and socioeconomic factors on the incidence of KEK. Subjects in this study were all pregnant women who visited the primary health clinics (puskesmas). The samples in this study were divided into two groups: the case group and the control group. The sample consisted of 90 respondents for the case, and double the 90 respondents for the control group, giving totally as many as 270 respondents. Inclusion criteria for the cases were pregnant women trimester I experienced KEK with a BMI less than 18.5 kg/m2. Literate and resided in the city of Metro. Exclusion criteria were which in trimester I pregnant women with disabilities and mental illness, and pregnant women with infectious diseases. As for the control group inclusion criteria trimester I pregnant women who did not experience KEK, BMI greater than or equal to 18.5 kg/m2, literate were and resided in the city of Metro. The exclusion criteria were pregnant women who experienced pain and stress, women who were not able to provide the information needed, and unwanted pregnancies. The research method used was a case control design (case control study). The results showed that age was not a significant influence on the incidence of KEK and KEK, with a p value of 0.170. There was no significant effect of parity on the incidence between KEK and KEK in pregnant women with a p value of 0.071, and gestational age did not have a significant effect on the incidence of KEK and KEK, with a p value of 0.429. There was a significant effect of education and occupation on the incidence of KEK and KEK in pregnant women with a p value of 0.001, and there was a significant effect between family size and income on the incidence of KEK and KEK in pregnant women with a p-value of 0.000. Multivariable analysis of the final model, parity has an influence on the incidence of KEK with p=0.003, OR=3.44 (CI: 1.54–7.70), there was the influence of the number of family memberson the incidence of KEK with p=0.001, OR=10.21 (CI: 2.97–35.12), and incomes howed the strongest effect with a value of p=0.001, OR=38.29 (CI: 14.15–103.61). There is no influence of demographic factors on the incidence of chronic energy deficiency in pregnant women, and there is influence of socioeconomic factors on the incidence of chronic energy deficiency in pregnant women. Keywords: chronic energy deficiency, demographic and socioeconomic factors Abstrak : Pengaruh Demografi dan Sosioekonomi pada Kejadian Kekurangan Energi Kronik IbuHamil Di Kota Metro Provinsi Lampung. Penelitian ini bertujuan untuk menganalisis pengaruh faktor demografi dan sosioekonomi pada kejadian KEK ibu hamil. Metode penelitian yang digunakan yaitu dengan rancangan kasus kontrol (case control study). Subjek pada penelitian ini seluruh ibu hamil yang berkunjung ke puskesmas yang ada di wilayah Kota Metro. Sampel dalam penelitian ini dibagi menjadi dua kelompok, yaitu kelompok kasus sebanyak 90 responden dan kelompok kontrol yaitu 180 responden yang telah memenuhi kriteria inklusi dan eksklusi penelitian. Hasil penelitian menunjukkan bahwa usia tidak berpengaruh signifikan dengan pada KEK ibu hamil, (p=0,170). Paritas tidak berpengaruh signifikan pada kejadian KEK ibu hamil, (p=0,071), dan usia kehamilan juga tidak berpengaruh signifikan pada kejadian KEK ibu hamil, (p=0,429). Terdapat pengaruh signifikan pendidikan dan pekerjaan pada kejadian KEK ibu hamil, (p=0,001). Terdapat pengaruh signifikan jumlah anggota keluarga dan pendapatan pada kejadian KEK ibu hamil, (p=0,001). Berdasarkan analisis multivariabel pada model akhir, paritas mempunyai pengaruh pada kejadian KEK ibu hamil (OR=3,44; IK: 1,54–7,70, p= 0,003). Terdapat pengaruh jumlah anggota keluarga pada kejadian KEK ibu hamil (OR= 10,21; IK: 2,97–35,12, p=0,001), dan pendapatan menunjukkan pengaruh yang paling kuat pada kejadian KEK ibu hamil (OR=38,29; IK:14,15–103,61, p=0,001). Tidak ada pengaruh faktor demografi pada kejadian KEK ibu hamil. Faktor sosioekonomi berpengaruh pada kejadian KEK ibu hamil. Kata kunci: Faktordemografidansosioekonomi, kekuranganenergikroon